Adsorption of CO, H2S and CH4 molecules on SnS2 monolayer: a first-principles study. (3rd April 2021) - Lin, Long; Chen, Ruixin; Huang, Jingtao; Wang, Pengtao; Zhu, Linghao; Yao, Linwei; Hu, Chencheng; Tao, Hualong; Zhang, Zhanying
ABSTRACT: The adsorption of CO, H2 S and CH4 on the intrinsic SnS2 monolayer and SnS2 monolayer with S-vacancy were studied by the first principle method. The most stable adsorption geometry was determined, and the electronic structure and differential charge were calculated. The results show that the band gap value of SnS2 monolayer with S-vacancy decreases and the surface activity increases. Compared with the intrinsic SnS2 monolayer, from the adsorption energy, electron transfer and adsorption distance of CO, H2 S and CH4 on SnS2 monolayer with S-vacancy, it can be seen that the S vacancy system is more sensitive to these gases. The results show that the SnS2 monolayer with S-vacancy is more sensitive to three gases, which provides a new design idea for SnS2 based gas sensor. As seen from the graphical abstract, the gas molecules (CO, H2 S, CH4 ) on SnS2 monolayer with S vacancy has stronger adsorption energy than the intrinsic SnS2 surface, and the adsorption properties of H2 S gas molecule on SnS2 monolayer with S-vacancy surface has the strongest adsorption energy −0.77 eV. It indicate that SnS2 monolayer with S-vacancy can be used as a promising gas detection material. Statement of article significance : First-principles studies were performed to investigate the electronic structures and adsorptive property of SnS2 monolayer and SnS2 monolayer with S-Vacancy with adsorbents CH4, CO and H2 S molecules. The adsorption order of the three gases on the intrinsic surface is H2 S > CH4 > CO. The adsorption order of the three gases on SnS2 monolayer with S-vacancy is H2 S > CO > CH4 . In addition, the results indicate that the adsorption energy of H2 S on SnS2 monolayer with S-vacancy is strong. The work provides a new design idea for SnS2 based gas sensor. GRAPHICAL ABSTRACT: UF0001